Disposal and application of discarded nitrile gloves in sustainable cement-based materials - Haoyu Tan; Baoping Feng; Yige Liu; Junyi Zhou; Junyao Liu; Songfu Yuan (Frontiers in Materials)
This study focuses on the application of shredded waste nitrile glove fibers (SWNGF) in sustainable cement-based materials, aiming to address the challenges of personal protective equipment (PPE) waste disposal and explore new uses in the construction sector. Specimens were prepared using Conch brand ordinary Portland cement as the base material, mixed with pure water, and incorporated with varying volumes (0%, 1%, 2%, and 3%) and sizes (15 mm × 5 mm, 20 mm × 5 mm, 15 mm × 10 mm) of SWNGF. Through compressive strength, flexural strength tests, and SEM analysis, the results revealed that both compressive and flexural strengths decreased with increasing SWNGF content, with the 15 mm × 10 mm size showing relatively better performance in terms of both compressive and flexural strength. Compressive strain initially increased and then decreased, with the 20 mm × 5 mm size favoring compressive strain. Flexural deflection increased steadily for Group A, followed by an initial increase and then a decrease for Group B, while Group C showed a consistent rise. Incorporating SWNGF improved flexural toughness, with post-failure results showing that specimens C3 at Td3 and Td5, and A3 at Td5 and Td10 performed better. Microscopically, the bond between the gloves and the cement matrix showed gaps, but the flexibility of the rubber improved performance. The surface characteristics of SWNGF facilitated bonding, and multiple hydration products were observed in the cement matrix, with some interconnected pores affecting the density. This study provides data support and theoretical basis for the application of SWNGF in concrete, holding significant potential for promoting the sustainable use of waste PPE in the construction industry.